Studying Writing Skills through Written Contexts of ESP - Gulomovna, Yakubova Lobar (Researchparks Publishing, 2023)
Writing gives us the energy we put on it, but if we know how to write papers or contexts in the field of engineering it enables us to improve our skills on it. Furthermore, writing help us to communicate with others online by expressing ideas, will to each other, sharing information. Writing is social performance through telegram or email or Facebook platforms where we may get a lot of knowledge to extend our views. We carried out with 30 participants at the faculty of oil and gas on the features of writing and its significance in their field of study.